Structural Equation Modeling Multigroup on Waste Economy Management - Anggun Fadhila Rizqia; Solimun Solimun; Nurjannah Nurjannah; Fachira Haneinanda Junianto; Kamelia Hidayat (UIN Sumatera Utara, 2025)
In recent years, urban waste has increased, leading to the demand for sustainable waste management based on circular economy. Facilities infrastructure and waste banks, play a role in improving 3R practices and the economic value of the community. This study used Structural Equation Modeling (SEM) with a Multigroup approach to analyze the effect of facility and infrastructure quality and waste banks on 3R-based waste management and waste economic management, moderated by environmental quality. In both groups, the impact of waste bank usage and 3R-based management was significant but stronger in moderate environments, with a significant difference (p-value = 0.032). Moderation also appeared in the influence of waste bank usage on waste economic management, where the difference was significant (p-value = 0.041). The results reveal that environmental quality moderates waste banks usage, 3R-based waste management and economic benefits, especially in environments with better quality.